2002
DOI: 10.1111/j.1744-7429.2002.tb00531.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cloud Combing and Shading by Isolated Trees in the Succession from Maquis to Rain Forest in New Caledonia1

Abstract: This study examined the role of shading and cloud combing of moisture by scattered trees of the emergent conifer Araucaria laubenfelsii (Corbass.) in montane shrubland‐maquis at Mont Do, New Caledonia, in facilitating the succession from shrubland to rain forest. Water collection experiments showed that these trees combed significant amounts of water from low clouds on days when no rainfall was recorded and deposited this moisture on the ground beneath the tree canopy. Analysis of photosystem II function in A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…Of equal or even greater significance might be the water fog interception and leaf water absorption by mature individuals, whose crown architecture does favor the interception of atmospheric water, by concentrating its green shoots in its upper and outer parts. Even though this interception has not yet been quantified in our target species, it has been for a taxonomically and ecologically related species from New Caledonia, Araucaria laubenfelsii (Rigg et al 2002). Trees of this species intercepted water from the atmosphere (cloud combing), thereby increasing soil moisture levels beneath their canopies in comparison to open areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of equal or even greater significance might be the water fog interception and leaf water absorption by mature individuals, whose crown architecture does favor the interception of atmospheric water, by concentrating its green shoots in its upper and outer parts. Even though this interception has not yet been quantified in our target species, it has been for a taxonomically and ecologically related species from New Caledonia, Araucaria laubenfelsii (Rigg et al 2002). Trees of this species intercepted water from the atmosphere (cloud combing), thereby increasing soil moisture levels beneath their canopies in comparison to open areas.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the evenly distributed annual precipitations (1200 to 2500 mm) that characterize the area of natural occurrence of the Brazilian pine (Carvalho 1994), root competition with grasses during the initial stages of tree development, under situations of forest expansion over grasslands, can limit water and nutrient availability (Espigares et al 2004). Also, plants in these environments can be under the influence of occasional periods of drought, and, in the adult stage, the great height attained by the species (up to~50 m; Reitz et al 1988) may impose limitations to soil water supply to the upper branches, because of the significant resistance due to friction and gravity (Burgess and Dawson 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the more uniform sapling species composition beneath Araucaria trees in relation to communities established beneath isolated shrubs ( Baccharis and Myrceugenia ) is likely to also be a consequence of trait variation between different ITS groups. For instance, Rigg et al (2002) found that the architecture of A. laubenfelsii trees scattered in maquis vegetation in New Caledonia increased soil moisture levels beneath their canopies by intercepting water from the atmosphere (cloud combing) and reduced photo‐stress suffered by saplings established beneath their canopies in relation to open sites. These effects might occur beneath canopies of A. angustifolia trees isolated in southern Brazilian grasslands, as both species live in habitats with similar environmental characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In New Caledonia, isolated trees of Araucaria laubenfelsii (Corbass.) were shown to intercept large amounts of water from low clouds, which resulted in deposition of water on the ground below their crowns (Rigg et al. 2002).…”
Section: Introductionmentioning
confidence: 99%